CLEOPATRA : I AM FIRE AND AIR - HAROLD BLOOM (NEW YORK SCRIBNER, 2017)
The second in a series of five short books about Shakespeare's most significant characters: Falstaff, Cleopatra, Lear, Iago and Macbeth.Offers an in-depth exploration of Shakespeare's character Cleopatra, delving into the complexities of her personality as well as how the author's understanding of her has evolved over the years.
Keywords: ANTONY AND CLEOPATRA-CRITICISM; CLEOPATRA